Outfit of The Day sebagai Personal Branding - Anaz Nur Puja; Maya Amalia Oesman P (Bandung Conference Series: Public Relations, 2022)
Abstract. Instagram is one of the most popular social media. With the presence of Instagram, there are various phenomena, one of which is the Outfit Of The Day (OOTD) phenomenon. Through this phenomenon, Instagram users use it as a way to build their personal branding. In this study, the researcher uses a qualitative descriptive research method with the object and subject of the research being an OOTD phenomenon on one of the Instagram accounts @cindyaudya which is the father of jajaka and the public relations officer of the West Java provincial government. The theory used in this research is Mantoya's Personal Branding Theory, as well as data collection from this research by interview, observation and literature study to obtain data related to research problems that have been traced, namely in the focus of this research. The results of this study, how to manage Outfit Of The Day in self-presentation from Cindy Audya in her Instagram account. Abstrak. Instagram menjadi salah satu media sosial yang paling banyak diminati. Dengan kehadiran Instagram menghadirkan berbagai fenomena, salah satunya fenomena Outfit Of The Day. Melalui fenomena ini, para pengguna Instagram menjadikannya sebagai sebuah cara untuk membangun personal brandingnya. Dalam penelitian ini, peneliti menggunakan metode penelitian deskriptif kualitatif dengan objek dan subjek penelitian merupakan fenomena Outfit Of The Day di salah satu akun Instagram @cindyaudya yang merupakan mojang jajaka dan public relations officer pemerintah provinsi Jawa Barat. Adapun teori yang digunakan dalam penelitian ini yakni Teori Personal Branding dari Mantoya, serta pengumpulan data dari penelitian ini dengan wawancara, observasi dan studi literatur untuk mendapatkan data terkait masalah penelitian yang telah dirunut yakni dalam fokus penelitian ini. Hasil dari penelitian ini, bagaimana pengelolaan Outfit Of The Day dalam presentasi diri dari Cindy Audya dalam akun Instagramnya.